Buddhist Principles Related to Political leadership of Local Administrators in Mueang District, Khon Kaen Province - Panyaparano (Riancharee), Phra Watcharaphum; Sawadta, Sutipong; Promkun, Suraphon (Journal of Buddhist Education and Research (JBER), 2025)
The objectives of this thesis were: 1) to study the level of political leadership among local administrators in Mueang District, Khon Kaen Province; 2) to examine the relationship between the Four Brahmavihāra and the political leadership of local administrators in Mueang District, Khon Kaen Province; 3) to explore the application of the Four Brahmavihāra to enhance the political leadership of local administrators in Mueang District, Khon Kaen Province. This research employed a mixed-method approach, integrating both quantitative and qualitative research methods. The quantitative research was conducted using a questionnaire as the primary tool for data collection. The sample group consisted of 399 local politicians in Mueang District, Khon Kaen Province. The statistical methods used for data analysis included frequency, percentage, mean, and standard deviation. Hypothesis testing was conducted using Pearson's correlation coefficient. The qualitative research involved in-depth interviews with 12 key informants, and the data were analyzed using descriptive content analysis. The research results were as follows: 1. The overall level of political leadership among local administrators in Mueang District, Khon Kaen Province, is high. When examining different aspects, it was found that all aspects were rated at a high level. The personality aspect had the highest mean score of 3.85, followed by morality and ethics (3.83), emotional intelligence (3.80), social skills, and knowledge and competency (3.68), respectively. 2. The relationship between the Four Brahmavihāra and the political leadership of local administrators in Mueang District, Khon Kaen Province, is statistically significant at the 0.01 level, with a positive correlation coefficient of 0.71. 3. Political leadership of local administrators in Mueang District, Khon Kaen Province, according to the principles of the Four Divine Abodes, local administrators should perform their duties and do so willingly, with good thoughts and compassion for the people in the area. They must be honest and sincere in their duties. They must consider the public interest as their main concern, be happy for others, and must perform their duties well, that is, help the people and meet them all the time. Performing duties must be done without bias.